Protein C in a patient with portal vein thrombosis in liver transplantation - S. V. Zhuravel; V. E. Aleksandrova; N. K. Kuznetsova; M. S. Novruzbekov; L. V. Donova (Трансплантология (Москва))
Background. The problem of thromboses, including those associated with impaired hemostasis system, is relevant in orthotopic liver transplantation.Aim. To present the experience of intraoperative use of protein C during orthotopic liver transplantation in a patient with a high risk of recurrent portal vein thrombosis.Results. During orthotopic liver transplantation in a patient with a high risk of recurrent portal vein thrombosis, the intraoperative administration of the protein C preparation at a dosage of 500 IU contributed to the increase in plasma level of protein C by 48%. In the post-transplant period, recurrent portal vein thrombosis was not observed. Conclusion. Intraoperative administration of protein C in combination with basic therapy for orthotopic liver transplantation helps to prevent recurrent portal vein thrombosis.